COLLABORATIVE GOVERNANCE PENANGANAN BAGI KORBAN KEKERASAN PEREMPUAN DAN ANAK MELALUI RUMAH AMAN KEMENTERIAN PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK - Tielung, Frangky; Nurdin, Nurliah; Sri, Neneng (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2023)
This study aims to identify and analyze the criteria and prerequisites for safe houses for women and children victims of violence with a victim's perspective and responsive to gender and to obtain a model of collaboration between government agencies (collaborative governance) in handling women and children victims of violence in safe homes. This study uses a qualitative method with a grounded theory approach. Data collection techniques were carried out by interviews and documentation. The data analysis technique uses qualitative analysis with 4 stages, namely data reduction, data collection, data presentation, and drawing conclusions. The results showed that the criteria and conditions for safe houses for women and children who were victims of violence had been regulated in the Pergub Prov. DKI Jakarta No. 44 of 2019 concerning Amendments to the Provincial Governor Regulation. DKI Jakarta No. 48 of 2018 concerning Safe Homes for Women and Children Victims of Violence, and can be divided into 3 (three) types of requirements, namely location and security requirements, infrastructure and physical facilities requirements, and service requirements. Referring to the perspective of victims and gender, the requirements for a safe house are safe and comfortable and able to meet all the needs of victims, both physical and non-physical. Collaborative models in safe houses require initial conditions accompanied by good institutional dimensions. In the facilitative leadership dimension, it is necessary to establish or appoint a leader and other administrators in a management structure who are responsible for coordinating and managing the collaboration process and in the collaboration process dimension, strengthening is carried out in the formation of inter-agency trust and commitment from each stakeholder.